One-to-one befriending for people with intellectual disability and symptoms of depression: protocol for a pilot randomised controlled trial. Issue 6 (21st June 2020) - Ali, Afia; Mckenzie, Emma; Hassiotis, Angela; Priebe, Stefan; Lloyd-Evans, Brynmor; Omar, Rumana; Jones, Rebecca; Panca, Monica; Fernandez, Vincent; Finning, Sally; Moore, Shirley; O'Connor, Danielle; et al.
Abstract : Introduction: People with intellectual disability (ID) are more likely to experience loneliness and have smaller social networks, which increases vulnerability to depression. Befriending may reduce depressive symptoms in other populations, but randomised controlled trials (RCTs) have not been carried out in this population. This pilot study aims to assess the acceptability and feasibility of carrying out a full RCT of one-to-one befriending by volunteers for people with ID, compared with an active control group. Methods and analysis: The trial aims to recruit 40 participants with ID. Participants in the intervention arm will receive weekly visits from a volunteer over 6 months. Community befriending schemes will recruit, train, supervise volunteers and match them to individuals with ID. Both groups will receive a booklet about local activities and have access to usual care. Health and social outcomes will be measured at the end of the intervention and 6 months' follow-up. The following outcomes will be assessed: (1) recruitment and retention of individuals with ID and volunteers in the trial, (2) adverse events related to the intervention, (3) the acceptability of the intervention, (4) whether the intervention is delivered as intended, (5) changes in health and social outcomes and (6) the feasibility of carrying out a cost-effectiveness analysis in a full trial. Qualitative data from participants, volunteers, staff and carers will identify barriers and facilitators of a future full trial. Ethics and dissemination: The study has been approved by the London City and East Research Ethics Committee (reference 18/LO/2188). The findings will be presented at conferences and published in a peer-reviewed journal and in the National Institute of Health Research journals library. A public engagement seminar will be held at the end of the study aimed at key stakeholders. Trial registration number: ISRCTN63779614 .